Analisis Strategi Diferensiasi Produk Haji dan Umrah dalam Menghadapi Persaingan Bisnis pada PT. Bimalyndo Hajar Aswad Cabang Bukittinggi - Weni Eka Putri; Santi Deswita (ARZUSIN, 2026)
Although product differentiation strategies in the Hajj and Umrah travel industry have received attention in several studies, research that specifically discusses the limited variety of products in affecting the competitiveness of travel agencies at the local level remains limited. This study aims to analyze the product differentiation strategy for Hajj and Umrah services in facing business competition at PT Bimalyndo Hajar Aswad Bukittinggi Branch. This study employed a qualitative approach with a case study design, involving informants consisting of the branch manager, employees, and pilgrims selected through a purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using an interactive data analysis technique through the stages of data reduction, data display, and conclusion drawing. The findings showed that the company had implemented a differentiation strategy based on service quality, such as assured facilities, worship comfort, the use of local muthawif, and a more meaningful travel experience. However, the limited variety of products became the main factor hindering competitiveness and contributed to the decline in the number of pilgrims. These findings contribute to the development of differentiation theory by emphasizing the importance of integrating service quality and product innovation in the religious services industry. The conclusion of this study emphasizes the importance of developing product variety and strengthening marketing communication strategies to enhance the company’s competitiveness. The implications of this study include theoretical contributions to enriching the sharia marketing literature as well as practical implications for actors in the Hajj and Umrah industry in designing more effective differentiation strategies, while also opening opportunities for further research related to digital marketing strategies and service innovation based on pilgrims’ needs.